2007
DOI: 10.1152/ajpheart.00549.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-κB improves left ventricular remodeling and cardiac dysfunction after myocardial infarction

Abstract: August 18, 2006; doi:10.1152/ajpheart.00549.2006.-Several studies have demonstrated that NF-B is substantially involved in the progression of cardiac remodeling; however, it remains uncertain whether the continuous inhibition of NF-B is effective for the prevention of myocardial remodeling. Myocardial infarction (MI) was produced by ligation of the left anterior coronary artery of rats. IMD-0354 (10 mg/kg per day), a novel phosphorylation inhibitor of I B that acts via inhibition of IKK-␤, was injected intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 35 publications
4
84
0
1
Order By: Relevance
“…As such, cardiac-specific deletion of Capn4, via prevention of IB degradation and NF-B activation, inhibits inflamma- tory responses and blocks both autocrine and paracrine signalings induced by local proinflammatory cytokines from cardiomyocytes, leading to a reduction in myocardial remodeling and an improvement of myocardial function in the MI heart. Given the critical role of NF-B signaling in cardiac remodeling (25,43), IB degradation and consequent NF-B activation may represent an important mechanism for calpain-mediated remodeling after MI. It is worthwhile to mention that calpain from cardiac fibroblasts may also contribute to post-MI myocardial remodeling because our recent study has revealed an important role of calpain in proliferation of cardiac fibroblasts (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, cardiac-specific deletion of Capn4, via prevention of IB degradation and NF-B activation, inhibits inflamma- tory responses and blocks both autocrine and paracrine signalings induced by local proinflammatory cytokines from cardiomyocytes, leading to a reduction in myocardial remodeling and an improvement of myocardial function in the MI heart. Given the critical role of NF-B signaling in cardiac remodeling (25,43), IB degradation and consequent NF-B activation may represent an important mechanism for calpain-mediated remodeling after MI. It is worthwhile to mention that calpain from cardiac fibroblasts may also contribute to post-MI myocardial remodeling because our recent study has revealed an important role of calpain in proliferation of cardiac fibroblasts (30).…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of IB frees NF-B dimmers and allows translocation of NF-B into the nucleus, where it can initiate transcription of target genes. Following MI, activation of NF-B contributes to maladaptive LV remodeling and functional deterioration by promoting inflammatory responses (25). Calpain activation has been demonstrated to induce IB degradation and NF-B activation (26,27).…”
Section: Myocardial Infarction (Mi)mentioning
confidence: 99%
“…Then the chest was closed, and the animals were allowed to recover in a warm, clean cage. 13 Rats that died within 24 h of the operation were excluded from this study.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…As an index of LV diastolic function, the ratio of the peak velocity of the early (E) to late (A) filling waves was determined from Doppler images of mitral flow obtained in the apical four-chamber view, as described previously. 13 Each value was the average of measurements over three consecutive beats, and data were obtained by blinded observers.…”
Section: Echocardiographymentioning
confidence: 99%
“…Many studies have shown that macrophage related inflammatory responses are increased by myocardial necrosis. 2,3) These inflammatory responses lead to an increase in fibroblasts and increased collagen synthesis. [4][5][6][7] Chlorogenic acid (8-tetrahydroxycyclohexacarboxylic acid, 3-(3,4-dihydroxycinnamate, CGA) is a key component of coffee.…”
mentioning
confidence: 99%